Formulation and Potency Extract Gel of Citrus Mistletoe Leaves (Dendrophthoe glabrescens (Blakely) Barlow) on Burn Wound Healing - Udayani, Ni Nyoman Wahyu; Dewi, Ni Kadek Dhea Cipta (Jurnal Kefarmasian Indonesia, 2025)
Second-degree burns require effective topical therapy to accelerate tissue regeneration and prevent infection. Mistletoe leaves (Dendrophthoe glabrescens (Blakely) Barlow) are traditionally used and are known to be rich in secondary metabolites such as flavonoids, saponins, and tannins, which have anti-inflammatory and antioxidant potential. This study aimed to evaluate the effectiveness of an ethanol leaf extract gel of (Dendrophthoe glabrescens (Blakely) Barlow) in healing second-degree burns in white mice (Mus musculus). The gel was formulated at extract concentrations of 5%, 10%, and 15%. A posttest-only control group design was employed, and the extract gel was applied for 14 days. The results demonstrated a significant increase in the percentage of wound healing, particularly at the 15% concentration, which approached the efficacy of the positive control. The flavonoid, saponin, and tannin activities in the (Dendrophthoe glabrescens (Blakely) Barlow) leaf extract play crucial roles in the healing process through anti-inflammatory, antibacterial, and antioxidant mechanisms, as well as by enhancing collagen synthesis. These findings suggest that this extract gel has potential as an effective alternative therapy for burn wounds.